Effect of transaction costs on market participation among smallholder cassava farmers in Central Madagascar - Okoye, B.C.; Abass, A.; Bachwenkizi, B.; Asumugha, G.N.; Alenkhe, B.; Ranaivoson, R.; Randrianarivelo, R.; Rabemanantsoa, N.; Ralimanana, I. (Informa UK Limited, 2016)
High transaction costs deter entry of small farmers into the market. With the data from 240 smallholder cassava farmers in Central Madagascar, this study identified strategies to promote successful smallholder commercialization. The coefficients for membership of cooperatives, native of community and farming experience, have a direct relationship with decision to participate in the market and which is significant at 1% level and road condition to the nearest town is good at 10% level. The coefficients for age, distance to the nearest town and distance from the farm to the market have an indirect relationship with decision to participate in the market and significant at 5, 10 and 1% levels, respectively. The results also show that the coefficients for personal means of transportation and marketing experience have a direct relationship with decision to sell cassava off-farm and at 10 and 1% level of significance, respectively, while distance to the nearest town and distance from the farm to the market had an indirect relationship with decision to sell off-farm at 5% level of significance each and cost of transportation at 1% level. The study raises policy issues which might reduce these transaction costs by providing more market outlets, better rural infrastructure and also bulking centres.